Neutropenia after the coadministration of clozapine and nirmatrelvir-ritonavir in a patient with SARS-CoV-2 infection: A case report with a literature review - Liu, Chun-I; Goh, Kah Kheng; Chen, Chun-Hsin (Frontiers in Psychiatry, 2022)
Background: Schizophrenia is considered one of the major risk factors for mortality from SARS-CoV-2 infection. Early antiviral treatment is important to decrease the risk of mortality. Currently, Paxlovid (nirmatrelvir-ritonavir) has been widely used in SARS-CoV-2 patients with risk factors. However, drug‒drug interactions with anti-psychotics are prominent and complicated. Case presentation: We report a clozapine-treated patient with SARS-CoV-2 infection who developed neutropenia after coadministration with Paxlovid. In this case, clozapine was used for over 15 years, without neutropenia development. However, severe neutropenia (absolute neutrophil count = 523/µl) developed 3 days after the coadministration of Paxlovid 2 doses per day, valproic acid 1000 mg per day and clozapine 100 mg per day. The development of neutropenia may be attributed to the complicated interaction among Paxlovid, SARS-CoV-2 infection, valproic acid, fluvoxamine and clozapine. Conclusions: Neutropenia is a rare but life-threatening event if a concomitant infection occurs. The risk may increase during SARS-CoV-2 infection and the coadministration of clozapine and Paxlovid. Although the exact causes of neutropenia in this patient are not fully clear, the white blood cell count and absolute neutrophil count should be closely monitored during the administration of Paxlovid in clozapine-treated patients with SARS-CoV-2 infection.